REKONSTRUKSI PERAN GURU PENDIDIKAN AGAMA DALAM MEMBENTUK KARAKTER SISWA DI TENGAH KRISIS MORAL REMAJA MODERN - Yanto, Andri; Holis Majid, Nur; Ihsan, Maulana; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study examines the reconstruction of the role of Islamic Religious Education (PAI) teachers as a response to the modern adolescent moral crisis, which is characterized by value disorientation due to the dominance of digital technology and popular culture. Using a qualitative approach based on library research framed within the perspective of Sociology of Ereignis, this research explores academic literature to dissect the ontological dynamics of teaching practices, digital ethical challenges, and the necessity for educator role transformation in the 21st century. Data were collected through document reviews and scholarly text analysis, then analyzed to construct a relevant teacher role model. The findings reveal that the current adolescent moral crisis is not merely behavioral delinquency, but a consequence of value alienation within virtual spaces. Therefore, religious teachers must transform from mere transmitters of theological content into